El periodismo escrito de contenido ambiental y su influencia para la conservación del río Babahoyo - León Rodríguez, Karla Maritza (2016)
The conflict between the constant development of humanity and the damage done to the environment is becoming more and more noticeable, the news media being a voice that should reflect the importance of caring for natural resources, however after a brief analysis of The local media, in particular those of the city of Babahoyo, could be evidenced the scarce coverage that is given to this particular problem in relation to the pollution that receives daily the Babahoyo River, which allows to configure the scientific question ¿ How does written journalism influence the conservation of the Babahoyo River? In order to know the answer, a field investigation was carried out in which the residents of the river banks participated, who stated that the dissemination of environmental content in the written media of the city is low, which concludes with the proposal of Carry out seminars for communication professionals to prepare themselves in relation to environmental issues, in order to increase the reports and environmental news that improve the work of communicating and with their messages to reduce the contamination of the affluent in the sector that was investigated.